2019
DOI: 10.3390/su11082370
|View full text |Cite
|
Sign up to set email alerts
|

Intersection of Physical and Anthropogenic Effects on Land-Use/Land-Cover Changes in Coastal China of Jiangsu Province

Abstract: China is experiencing substantial land-use and land-cover change (LUCC), especially in coastal regions, and these changes have caused many ecological problems. This study selected a typical region of Jiangsu Province and completed a comprehensive and detailed spatial-temporal analysis regarding LUCC and the driving forces. The results show that the rate of land-use change has been accelerating, with land-use experiencing the most substantial changes from 2005 to 2010 for most land-use types and the period from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 62 publications
2
8
0
Order By: Relevance
“…(1) At the patch-class level, the landscape pattern evolution characteristics of industrial rural areas in Southern Jiangsu were that construction land had continuously encroached on green and cultivated land in all four study areas, exhibiting trends of expansion, centralization and the continuous consolidation of small patches into large patches during evolution and ultimately replacing cultivated land as the dominant landscape category. The result was in accordance with those in the studies of Yang, Sun et al, Ma et al, Xu et al and Chuai et al [31][32][33][34][35]. The reasons might be as follows: (1) Relevant studies showed that under the background of rapid socio-economic development, urban master planning is constantly updated, and relevant policies and regulations constantly promote human beings to expand the scope of urban built-up areas through deforestation, farmland reclamation and civil construction.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…(1) At the patch-class level, the landscape pattern evolution characteristics of industrial rural areas in Southern Jiangsu were that construction land had continuously encroached on green and cultivated land in all four study areas, exhibiting trends of expansion, centralization and the continuous consolidation of small patches into large patches during evolution and ultimately replacing cultivated land as the dominant landscape category. The result was in accordance with those in the studies of Yang, Sun et al, Ma et al, Xu et al and Chuai et al [31][32][33][34][35]. The reasons might be as follows: (1) Relevant studies showed that under the background of rapid socio-economic development, urban master planning is constantly updated, and relevant policies and regulations constantly promote human beings to expand the scope of urban built-up areas through deforestation, farmland reclamation and civil construction.…”
Section: Discussionsupporting
confidence: 92%
“…Among the four study areas, Kunshan exhibited the most significant landscape pattern evolution characteristics. This result was also in accordance with the results of the studies by Yang, Sun et al, Ma et al, Xu et al and Chuai et al [31][32][33][34][35]. The reason for the results might be as follows: (1) The gradual improvement of a traffic network would cause disorderly cutting of the original patch landscape, which seriously affects the circulation of the ecological function of the regional landscape.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The change of land nature leads to the deterioration of ecological environment and affects urban precipitation and temperature. At the same time, the conversion of land use types in China has accelerated the disappearance of grassland and forest land types, which is not conducive to the development of urban carbon emission reduction [30].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The 36 Q participants completed the Q sorting, in which 25 samples were valid. The sample size was reasonable and met the research criteria [30].…”
Section: Nomentioning
confidence: 99%